Non-invasive Investigation of Segment C of the Krzemionki Exploitation Field. Initial Research Results - Jedynak, Artur; Wroniecki, Piotr (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2022)
Non-invasive research has been undertaken in the southern arm of the archaeological area of the Krzemionki exploitation field, which is one of the least excavated of its regions. Geophysical prospection covered an area of 3.5 ha, and in addition, an area of more than 5 ha was examined by surface collection. The image of the underground structures was obtained thanks to a comprehensive comparison of the results of magnetic, earth resistance and GPR measurements, as well as the distribution of archaeological finds on the ground surface. The study was supplemented with data obtained from the analysis of archival aerial photos and Airborne Laser Scanning (ALS) derivatives. On the basis of these complementary data, it was possible to create a general image of the distribution of archaeological sources in the study area. When trying to determine the potential range of the exploitation field, the most legible results were obtained from earth resistance survey and magnetic gradiometry methods. In the most fully explored fragment of the area, anomalies suggesting the presence of prehistoric mining facilities are located in a strip 40–60 m wide, running in the NW-SE direction. Surface studies showed the presence of anthropogenic limestone debris in a zone of similar width (50–75 m) and the direction of its course, while the spread of flint and erratic stone finds turned out to be even greater (a belt 70–90 m wide). Geophysical surveys indicate the possibility of the existence of flint workshops and settlement facilities around the mining field. This can be confirmed in future by further systematic studies of its surroundings.
il. ; 24 cm
Keywords: archeologia -- czasopisma; Krzemionki; exploitation field; non-invasive research; striped flint